The virtuous cycle of news sharing on Facebook: Effects of platform affordances and journalistic routines on news sharing - dos Santos, Marcelo Alves and Lycarião, Diógenes and de Aquino, Jakson A (New Media & Society, 2019)
A growing body of literature shows how important content is in terms of news sharing. Nevertheless, the same literature overlooks the theory and corresponding effects on audience metrics produced by news routines adapted to platform affordances. This article aims to contribute to closing this gap by investigating 99 Facebook news pages covering 13 countries ( n posts = 823,184). Causality tests demonstrate that a combination of posting regularity, the use of native video and balance of posting may lead to a virtuous cycle of news sharing. Since this is not a trivial endeavour, we conclude that success of news media requires strategic planning of news routines to make them suitable to each platform. In terms of implications for future research, the accumulated knowledge on news sharing should be reassessed since our data show that the same content has greater chances of being shared according to the variables investigated in this research.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNDYxNDQ0ODE4Nzk3NjEw